Performance evaluation of Gurez sheep in farmer’s flocks—A threatened sheep breed of Kashmir - RATHER, MUBASHIR ALI; AHANGER, SHOWKAT AHMAD; HAMADANI, A; SHAH, M MAROOF; BABA, MOHMMAD ASHRAF; KHALEEL, MUSTAFA (The Indian Journal of Animal Sciences, 2021)
Gurez is an indigenous breed of sheep native to the Gurez Valley of J&K, India. Despite being a unique genetic resource, this breed is largely unexplored and meagre studies have been conducted on it. Hence, a comprehensive study was conducted to study the breed in its native breeding tract. Data on growth, wool, reproduction and morphometric traits of Gurez sheep maintained under farmers' flocks in its native tract were recorded and analyzed for performance evaluation as well as the farming practices in that area with regards to the breed. Screening for parasites and brucellosis, blood biochemistry and mineral profile were also conducted. This triple purpose breed produces milk, meat as well as apparel quality wool. The average values for wool traits were 76.12, 28.31, 4.42, 5.35 and 8.18 for clean wool yield (CWY) (%), fibre diameter (FD) (Î¼), staple length (SL) (cm), crimps per cm (NCPC) and medullation (%), respectively. The coefficient of variations % of these traits ranged from low to very high indicating that the traits had low to very high variability. The least squares mean for clean wool yield (%), fiber diameter (μ), staple length (cm), crimps per cm and medullation (%) were 77.07±0.33, 29.83±0.41, 4.80±0.17, 5.04±0.28 and 9.26±0.79, respectively. The sexual dimorphism was observed in favour of males with respect to all these traits. Age had non-significant effect on these traits in the present study. Black wool samples were having higher estimates of FD, CWY (%), SL and medullation (%). NCPC was higher for white wool samples. Conservation of this unique breed and its selective breeding is highly recommended. The incidence of Eimeria (37.50%) was found to be highest in the area.